Pengaruh Pemberian GnRH pada Sapi Potong yang Mengalami Kawin Berulang (Repeat Breeding) - Surya Agus Prihatno; Sri Gustari; Asmarani Kusumawati; Agung Budiyanto; Erif Maha Nugraha Setyawan; Yosua Kristian Adi (Jurnal Sain Veteriner, 2021)
Repeat breeding is a condition in which cows have normal estrous cycles and have been mated 3 times or more but are not pregnant. The incidence of repeat breeding in beef cattle can be detrimental to breeders in terms of time, that the calving period becomes longer so that the cows cannot give birth to calves once a year. Various ways to deal with repeat breeding have been done, but the results are not optimal. This study was conducted to determine the effect of Gonadotrophin Releasing Hormone (GnRH) in cows with repeat breeding. A total of fifteen beef cattle with repeat breeding were used in this study. The cows were divided into 3 groups of 5 each. Cows that were estrus in the first group (as a control group) were only performed artificial insemination (AI) without GnRH injection. In the second and third groups, after AI, they were injected with GnRH at AI time and 3-4 days after AI with a dose of 5 ml (Fertagyl®, 500 µg gonadorelin) intramuscularly. A pregnancy examination was carried out three months later and the results were recorded. The data obtained were analyzed descriptively and quantitatively using Chi-Square statistical analysis. The results of the analysis showed that there were differences in the pregnancy rate in the first group (control) with the second cow group and the third cow group, which were 20%, 80%, and 60% respectively. Based on statistical analysis, there was a significant difference in pregnancy rate (P <0.05) between the three groups. It was concluded that GnRH administration could increase the pregnancy rate in beef cattle that had repeat breeding.